PENGEMBANGAN MODUL KETERAMPILAN DASAR MENGAJAR KIMIA BERBASIS PENDEKATAN SAINTIFIK DI PROGRAM STUDI PENDIDIKAN KIMIA UNIVERSITAS MUHAMMADIYAH PONTIANAK - Nurul Huda; Tuti Kurniati; Dini Hadiarti; Dedeh Kurniasih (Universitas Muhammadiyah Pontianak, 2019)
This study aimed to produce a module of basic chemistry teaching skills based on a valid and practical scientific approach. Using an R&D model of 3-D, three out of four stages of material design were employed, they were Define, Design, and Develop stages. The data collection technique used in this study were interviews and indirect communication. The instruments were interview guides, validation questionnaires, and student response questionnaires. The study was obtained : (1) the validity of material aspects was 95% and the validity of media aspects was 97.22% with very valid criteria; (2) the practicality of the module from individual trials was 96% and from the small group trials was 81.06% with very practical criteria. In conclusion, the module of basic chemistry teaching skill based on scientific approach is appropriate to be used in the subject of Basic Ability to Teach Chemistry.